Issues in research perceptions of successful academic women - Soliman, Izabel (New South Wales : University of New England, 1998)
Disscussion by 7 academic women from University of New England who were active in research and have the succesfull attracting research program. They share their advantage of being situated at the university
Keywords: Women in education; Women -- Educatin (Higher); Women teachers